Transition to palliative care when transcatheter aortic valve implantation is not an option: opportunities and recommendations. Issue 1 (March 2016) - Lauck, Sandra B.; Gibson, Jennifer A.; Baumbusch, Jennifer; Carroll, Sandra L.; Achtem, Leslie; Kimel, Gil; Nordquist, Cindy; Cheung, Anson; Boone, Robert H.; Ye, Jian; Wood, David A.; Webb, John G.
Abstract : Purpose of review: Transcatheter aortic valve implantation (TAVI) is the recommended treatment for most patients with symptomatic aortic stenosis at high surgical risk. However, TAVI may be clinically futile for patients who have multiple comorbidities and excessive frailty. This group benefits from transition to palliative care to maximize quality of life, improve symptoms, and ensure continuity of health services. We discuss the clinical determination of utility and futility, explore the current evidence guiding the integration of palliative care in procedure-focused cardiac programs, and outline recommendations for TAVI programs. Recent findings: The determination of futility of treatment in elderly patients with aortic stenosis is challenging. There is a paucity of research available to guide best practices when TAVI is not an option. Opportunities exist to build on the evidence gained in the management of end of life and heart failure. TAVI programs and primary care providers can facilitate improved communication and processes of care to provide decision support and transition to palliative care. Summary: The increased availability of transcatheter options for the management of valvular heart disease will increase the assessment of people with life-limiting conditions for whom treatment may not be an option. It is pivotal to bridge cardiac innovation and palliation to optimize patient outcomes.